Latin America in the Twentieth Century - Calvert, Peter. author. aut Link
XII, 244 p.
Keywords: Earthquakes, guerrillas and military coups hit the headlines; the underlying social order passes almost unnoticed. As we move towards the end of Latin America's second century of independence, much about this fascinating area remains a mystery. Yet Latin America has led the way for the Third World to demand full equality for its citizens. In Latin America in the Twentieth Century two specialists in Latin American politics present a new view of this vital region, its frustrations, its setbacks and its possibilities.